Instructional materials used in teaching mathematics: Basis for enhancing mathematics program - Tuliao, Jocelyn D. (International Journal of Psychosocial Rehabilitation, 2020)
This paper aimed to ascertain the instructional materials used in teaching Mathematics. Quantitative research method was used in identifying and finding the Mathematics teachers’ profile, instructional materials used by the Mathematics teachers in teaching Mathematics, extent to which Mathematics teachers use instructional materials in their teaching, issues and concern in the utilization of instructional materials in teaching Mathematics and effectiveness of instructional materials in teaching Mathematics as assessed by the school heads, Mathematics teachers and students of four (4) public high schools in Sto. Nino, Piat and Tuao, Cagayan. Findings of the study showed that majority of the respondents perceived that instructional materials are very effective in teaching Mathematics. It is found out that there is no significant difference on the extent of utilization of instructional materials in teaching Mathematics when grouped according to their highest degree earned, number of years in teaching Mathematics and Mathematics subjects taught while there is a significant difference on the extent of utilization of instructional materials in teaching Mathematics when grouped according to their age, number of seminars attended for the past five years and awards received. Results further showed that the issues and concerns in the utilization of instructional materials in teaching Mathematics as revealed by the Mathematics teachers are the following. There is no wide array of guides, manuals and journals for use, lack of instructional materials in school, poor motivation on the use of instructional materials and lack of resource centers in the schools. Results further revealed that the three groups interviewed had commonality in the manner of how they look at the effectiveness of instructional materials in teaching Math. It was mentioned that instructional materials encourage participation of students in class discussion. Moreover, it makes learning real and permanent, promote longer retention and can concretize concepts for effective learning. Keywords: , ,